2006
DOI: 10.1152/ajpheart.00660.2005
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory role of ovarian sex hormones in calcium uptake activity of cardiac sarcoplasmic reticulum

Abstract: Bupharesponsiveness, was demonstrated in ovariectomized hearts. In parallel measurements of SERCA activity in SR-enriched membrane preparations from ovariectomized hearts, a suppressed maximum SERCA activity with a leftward shift in the relationship between pCa (-log molar free Ca 2ϩ concentration) and SERCA activity was also detected. A significant downregulation of SERCA proteins and reduction in the SERCA mRNA level were observed in association with suppressed maximum SERCA activity. While there were no cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
80
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(93 citation statements)
references
References 40 publications
13
80
0
Order By: Relevance
“…Here we attempted to decipher the molecular mechanism of SERCA2a regulation by progesterone at the cellular level. We also observed a moderate 1.5-fold increase in SERCA2a protein levels in NRbCM, which is consistent with our findings and those of other researchers (4). This increase in SERCA2a protein levels was not associated with changes in mRNA levels, suggesting that the effect of progesterone is posttranslational.…”
Section: Casupporting
confidence: 93%
See 1 more Smart Citation
“…Here we attempted to decipher the molecular mechanism of SERCA2a regulation by progesterone at the cellular level. We also observed a moderate 1.5-fold increase in SERCA2a protein levels in NRbCM, which is consistent with our findings and those of other researchers (4). This increase in SERCA2a protein levels was not associated with changes in mRNA levels, suggesting that the effect of progesterone is posttranslational.…”
Section: Casupporting
confidence: 93%
“…Furthermore, supplementation with estrogen and progesterone restored SERCA2a mRNA levels, protein expression levels, and pump function (4). Recently, our laboratory showed that SERCA2a protein levels were moderately upregulated in progesterone-treated ovariectomized transgenic female LQT2 rabbits (20).…”
Section: Camentioning
confidence: 87%
“…We (6,7) have previously demonstrated that chronic deprivation of female sex hormones induces a suppression in intracellular Ca 2ϩ transients together with a decrease in SERCA activity. Interestingly, in the present study, maximum SERCA activity of the heart of male sham rats was similar to that detected in ovariectomized rats (6), suggesting a lower SERCA activity in the male heart than in the female heart during young age.…”
Section: Discussionmentioning
confidence: 99%
“…SR membrane vesicles were prepared from left ventricular homogenates as previously described (6). In brief, the left ventricle was minced and homogenized in iced-cold 10 mM NaHCO 3 buffer (pH 6.8) containing a cocktail of protease inhibitors.…”
Section: Methodsmentioning
confidence: 99%
“…Estrogen receptors are expressed on cardiomyocytes (82), thus cardiomyocyte function could be directly affected by estrogen levels. Estrogen has also been shown to significantly suppress SERCA2 expression in ovariectomized rats compared to controls, thus altering cardiac myocyte sarcoplasmic reticulum calcium uptake (83). In the latter study, investigators noted that estrogen and progesterone supplementations were equally effective in preventing changes in ovariectomized hearts.…”
Section: Female Predominance Related To Hormonesmentioning
confidence: 96%